5G technology : 3GPP new radio - Holma, Harri; Holma, Harri, 1970-; Toskala, Antti; Nakamura, Takehiro, 1965- (Hoboken, NJ : John Wiley & Sons, Inc., 2020)
"Long Term Evolution (LTE) networks were launched commercially 2009 and the technology turned out to be hugely successful for boosting mobile broadband capabilities. Global mobile data traffic has grown by a factor of 10 during the last 5 years. LTE has enabled large number of new applications in smartphones and has brought high speed internet access to hundreds of millions of people that never had internet access earlier. 5G targets are set far beyond LTE in terms of technical capabilities and potential use cases. 5G is designed to provide ultra reliable low latency communication which opens completely new application areas for enterprise communication, like remote control, or for consumer communication like esports and cloud gaming. 5G will also boost mobile broadband performance to data rates beyond 10 Gbps. Those impressive targets require new solutions for the 5G mobile networks including new spectrum options, new antenna structures, new physical layer and protocols designs and new network architectures. Deep understanding of the underlying 5G technology allows to take full benefit of new capabilities. This book describes details of 5G specifications and practical deployment aspects. We hope you enjoy reading the book!"--
Includes bibliographical references and index.
Keywords: 5G mobile communication systems